2020
DOI: 10.1017/s1751731120000099
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies quantitative trait loci regions involved in muscle acidic profile in Large White heavy pigs

Abstract: The widespread use of genome-wide association studies resulted in the discovery of genomic regions associated with fatty acid (FA) composition in different porcine tissues, but little information exists about the genes involved in FA composition of meat obtained from heavy pigs selected for the production of Italian dry-cured hams. To this objective, we genotyped with a single nucleotide polymorphism (SNP) panel 795 Italian Large White heavy pigs to identify the markers and genomic regions associated with Semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…2006; Sellier, Maignel, & Bidanel, 2010), and in Duroc pigs slaughtered at about 125 kg live weight (Ros-Freixedes, Reixach, Bosch, Tor, & Estany, 2014). Recent studies carried out on Italian Large White (ILW) heavy pigs (slaughtered at about 155 kg live weight) found that the FA composition of fat stored in muscle and backfat (BF) are the result of moderately heritable traits (Davoli et al, 2019;Zappaterra et al, 2020) and associated with genetic markers (Zappaterra, Ros-Freixedes, Estany & Davoli, 2018;Catillo et al, 2020). Diet has also a major role in the variability noticed in pork FA composition, as proved by the considerable literature produced over the years (Morgan, Noble, Cocchi, & McCartney, 1992;Leskanich, Matthews, Warkup, Noble, & Hazzledine, 1997;Carrapiso, Tejeda, Noguera, Ibáñez-Escriche, & González, 2020).…”
mentioning
confidence: 99%
“…2006; Sellier, Maignel, & Bidanel, 2010), and in Duroc pigs slaughtered at about 125 kg live weight (Ros-Freixedes, Reixach, Bosch, Tor, & Estany, 2014). Recent studies carried out on Italian Large White (ILW) heavy pigs (slaughtered at about 155 kg live weight) found that the FA composition of fat stored in muscle and backfat (BF) are the result of moderately heritable traits (Davoli et al, 2019;Zappaterra et al, 2020) and associated with genetic markers (Zappaterra, Ros-Freixedes, Estany & Davoli, 2018;Catillo et al, 2020). Diet has also a major role in the variability noticed in pork FA composition, as proved by the considerable literature produced over the years (Morgan, Noble, Cocchi, & McCartney, 1992;Leskanich, Matthews, Warkup, Noble, & Hazzledine, 1997;Carrapiso, Tejeda, Noguera, Ibáñez-Escriche, & González, 2020).…”
mentioning
confidence: 99%
“…SCD gene: Stearoyl-coenzyme A desaturase gene ( SCD ) is a functional gene that encodes an important enzyme stearoyl-CoA desaturase necessary for the conversion of saturated fatty acids (SFAs) into monounsaturated fatty acids (MUFAs) [ 92 ]. The SCD gene has been associated with the fatty acid composition of porcine longissimus dorsi muscle [ 79 ], and acts as an important regulator of the genetic mechanism of lipid deposition and fatty acid synthesis in pigs [ 77 , 82 , 92 ]. Additionally, it is involved in the PPAR signalling pathway and is important for meat quality traits in pigs [ 72 ].…”
Section: Genes Involved In Fat Metabolism and Imf Accretion In Pigsmentioning
confidence: 99%
“…The overall selection goal in modern breeding programs is directed to improving qualitative and quantitative features that are economically important in pork production. As pork quality is influenced by many genetic and non-genetic factors, many studies have been focused on revealing the genetic background and its various genetic factors (Guy et al 2012;Piórkowska et al, 2018;Ropka-Molik et al 2018;Catillo et al 2020). Increases in societal pressure for sustainable pork production highlight the need for alternative, more holistic approaches in genetic selection programs, that will enable the production of high-quality meat, while maintaining performance and carcass characteristics of pigs at a satisfactory level (Merks et al 2012).…”
Section: Traits Meat Qualitymentioning
confidence: 99%